2017
DOI: 10.4271/2017-24-0057
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Control of BMEP and NOx Emissions in a Euro VI 3.0L Diesel Engine

Abstract: A model-based approach to control BMEP (Brake Mean Effective Pressure) and NOx emissions has been developed and assessed on a FPT F1C 3.0L Euro VI diesel engine for heavy-duty applications. The controller is based on a zero-dimensional real-time combustion model, which is capable of simulating the HRR (heat release rate), incylinder pressure, BMEP and NOx engine-out levels. The real-time combustion model has been realized by integrating and improving previously developed simulation tools. A new discretization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(60 citation statements)
references
References 33 publications
0
60
0
Order By: Relevance
“…• Finally, it was demonstrated that the proposed method is physically consistent, since it maintains a high accuracy even when the number of points used for calibration is very low, and that it requires a much smaller computational time than the previous model proposed in [8].…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…• Finally, it was demonstrated that the proposed method is physically consistent, since it maintains a high accuracy even when the number of points used for calibration is very low, and that it requires a much smaller computational time than the previous model proposed in [8].…”
mentioning
confidence: 87%
“…After a general discussion about the NOx formation process and some recalls on the previous semi-empirical NOx model proposed by the authors in [8] (Section 3.1), the identification of the input variables of the proposed NOx model is described in Section 3.2, while the NOx model is presented in Section 3.3. Section 3.4 reports a quick summary on the predictive combustion model that is necessary to adopt when using the previous semi-empirical NOx model described in [8].…”
Section: Model Descriptionmentioning
confidence: 99%
See 3 more Smart Citations